Physicochemical and Anti-nutrients Analysis of Pasteurised and Unpasteurised Underutilised Sweet Potato Haulm Juice Powder - Nurhani Fatihah Binti Mohd Hanifah; Mansor Syamila (USIM Press, 2024)
Malaysian Journal of Science, Health & Technology (MJoSHT) Volume 9 No 2 Page (112-119)